ESTIMASI PARAMETER DARI DISTRIBUSI LOMAX MENGGUNAKAN METODE BAYESIAN ENTROPY LOSS FUCTION - Sani, Ridha Fadhila; Yanuar, Ferra; Devianto, Dodi (LPPM Universitas Bina Bangsa, 2024)
The purpose of this research is estimating shape parameter (θ) of Lomax distribution with known shape parameter (β). Estimating parameter of Lomax Distribution using Bayesian Entropy Loss Function method with Gamma prior as conjugate prior of parameter (θ). The data used in this research is generated data which is obtained from R-Studio. Estimating parameter with Bayesian Entropy Loss Function Method from Lomax distribution with used shape parameter (θ=1) is and estimating parameter with Bayesian Entropy Loss Function Method from Lomax distribution with used shape parameter (θ=1,5) is . Estimating shape parameter (θ) will be evaluated used AIC, AICc, and BIC method